Pelatihan Virtual Peningkatan Self Awareness untuk Meningkatkan Kualitas Hidup pada Teman Tuli sebagai Dampak Pandemic Covid 19 - Eva Meizara Puspita Dewi; Basti Basti; Eka Sufartianinsih Jafar (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. This Community Partnership Program (PKM) is the NGO of Human Nobel Makassar. The problems faced are: Social interaction, limitations in communicating verbally make it often less able to understand the intentions of the people in the surrounding environment so that what they feel is ignored or rejected. The phenomenon of the Covid 19 pandemic, where there are rules about social distancing, wearing masks and so on, makes it even more obstacles in social interaction. This condition makes them find themselves depressed and insecure with the result that they feel meaningless in life. The quality of their life has decreased and they tend to blame themselves more. Therefore, self-awareness training is needed to help them realize their existence and how to be able to respond it in order for them to live more meaningful and quality life. The methods used: The training was carried out in 3 sessions until these deaf could appreciate the content of the material well and then provided assistance within 2 weeks after that. The results achieved were an increase in self-awareness of them before and after the training which was reflected in the results of the pretest and posttest, namely the participants' self-awareness before training was 35 points, up to 135 points.